GC-MS Analysis of Active and Applicable Compounds in Methanol Extract of Sweet Star Fruit (Averrhoa carambola L.) Leaves - Ni Putu Adriani Astiti; Yan Ramona (Bogor Agricultural University, Indonesia, 2021)
The leaves of star fruit plants (Averrhoa carambola) have been traditionally used to cure many diseases, such as hypertension and fever. Besides, the leaves of this plant have also widely been used as the main raw material in lawar (a Balinese traditional food) making. In this research, the methanol extract of this plant leaves was analyzed and identified for active compound contents. The main objective of this research was to investigate types of possible active and applicable compounds contained in such leaves, previously extracted/macerated in methanol solution. Analysis was conducted by applying GC-MS instrumentation using methanol solution. The results showed that 10 possible active and applicable compounds (Butane, 1,1-diethoxy-3 methyl-(CAS)1.1-DII, Dodecanoic acid, methyk ester(CAS) methyl, Dodecanoic acid, methyl ester (CAS) Ethyl Laun, Pentadecanoic acid ethyl ester, Hexadecanoic acid methyl ester (CAS) Methyl pa, OCTADECA 9.12 DIENOIC ACID METHYL, 9-Octadecenoic acid methyl ester (E)-(CAS), Octadecanoic acid methyl ester, and (E) 9-Octadecanoic acid ethyl ester) were identified in methanol extract of such leaves. Among those compounds, Butane, 1,1-diethoxy-3-methyl and Hexadecanoic acid, methyl ester was two most abundance constituents with percentage of peak areas of 35.67% and 26.93%, respectively.